Designing an Effective Schools Model based on learning Organizational Model in Primary Schools - ZahediPour, Masoud; Oladian, Masoumeh; Hosseini, Seyed Rasoul (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to design an effective school model based on the model of learning organization in primary school in Tehran.Methodology: The research method was a combined research method (qualitative and quantitative) by grounded theory method and structural equation model by quantitative method. The research population was in the qualitative section of university professors specializing in primary education and in the quantitative section were experts in the field of education in Tehran in 2009-2010. Twelve people were selected as a sample in the qualitative section by purposeful method from university professors and 196 experts and specialists in education in Tehran were selected by multi-stage cluster sampling. The research tool was a semi-structured interview in the qualitative part of the interview and a researcher-made questionnaire in the quantitative part of the effectiveness of the learning schools. The data were analyzed in the qualitative part by the grounded method of exploratory theory and in the quantitative part by the structural equation model test and factor analysis.Findings: The results showed that the model of confirmatory factor analysis of the first stage and the relevant factor were: empowerment of human resources (with a factor of 0.926), establishment of teaching and learning system (with a factor of 0.910), extracurricular activities (with a factor of 0.914), Competencies of managers (with a factor of 0.910), competencies of teachers (with a factor of 0.978), educational policies (with a factor of 0.934), technological facilities (with a factor of 0.905).Conclusion: Based on the research findings, it can be said that the priority factors of effective schools are: First priority: Empowerment of human resources, Second priority: Establishment of teaching and learning system, Third priority: Extracurricular activities, Fourth priority: Competencies of principals, Fifth priority: Teachers' competencies, Sixth priority: Educational policies, Seventh priority: Technological facilities.